Protective coatings for carbon bonded carbon fibre composites - Smeacetto, F.; Ferraris, M.; Saivo, M.; Ellacott, S. D.; Ahmed, A.; Rawlings, R. D.; Boccaccini, Aldo R. (Ceramics International, 2008)
Carbon bonded carbon fibre composites (CBCF) were modified by direct reaction with molten silicon in order to obtain a silicon carbide layer on the composite surface. Subsequently, the Si-infiltrated CBCF material was coated with a silica-based glass containing yttria and alumina by means of a slurry-dipping technique. On heat treatment the glass yielded a glass-ceramic layer thus giving a multi-layered oxidation and erosion protection system. The microstructural characterisation of the coating was conducted by standard microscopy techniques and by X-ray diffraction. The controlled crystallization of the glass-produced cristobalite, yttrium silicate (Y2Si2O7, keiviite, β-form) and mullite as main crystalline phases. These are excellent ceramic materials for oxidation and erosion protection of SiC-coated carbon-based composites since their coefficients of thermal expansion (CTE) closely match that of SiC. The possibility of healing (closure) of micro cracks by a thermal treatment at 1375 °C, thus exploiting the viscous flow of the residual glass in the glass-ceramic, was explored in order to extend the service life of the protection system. © 2007 Elsevier Ltd and Techna Group S.r.l.
UnivIS-Import:2015-03-09:Pub.2008.tech.IW.LM.protec
Keywords: Carbon matrix composites; D. Glass ceramics; Oxidation protection; Slurry infiltration